Risk Management Practices and Financial Performance: The Case of Banks in Sultanate of Oman - Essia Ries Ahmed; Shima Hamdan AL Mamar; Ahad Said AL Ghassani (Postgraduate Program Merdeka University, 2021)
The main objective of this project is to define the relationship between risk management practices and a bank's financial performance. This is a quantitative study, where the quantitative data was collected via secondary data. Data collection from the annual reports of banks in Muscat Securities Market (MSM).The Sample size of 8 banks. In this research, data collected is analyzed using Structural Equation Modelling (SEM) with Partial Least Square PLS Software. The findings revealed that risk management is positively meaningful while avoiding risk.The findings pointed that the risk management has significant with a ROA. This result indicates that management has a significant influence on banks performance (ROA). As well as, the findings found that the risk management insignificant with a (ROE)